Sprecherbezeichnungen im Kyklops des Euripides - Seidensticker, Bernd (Hyperboreus, 2019)
The designation of speakers in the manuscripts of dramatic texts – either by abbreviated names or by a paragraphos is notoriously unreliable. The paper discusses the cases in Euripides’ Cyclops, where the assignment of a line resp. of lines to a certain dramatis persona is controversial, and looks at potential divisions of the chorus.